2017
DOI: 10.1111/den.12824
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided celiac plexus block and neurolysis

Abstract: Endoscopic ultrasound-guided celiac plexus neurolysis (EUS-CPN) is widely used for reducing pain originating from upper abdominal organs. It is mainly indicated to treat pancreatic cancer pain, but also to relieve pain as a result of chronic pancreatitis. Real-time guidance and color Doppler imaging by EUS made the procedure easier and safer, resulting in greater pain relief. Currently, two techniques are used for EUS-CPN. The classic approach, known as the central technique, involves injection of a neurolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“… 40 Recently, endoscopic ultrasound (EUS) has become a preferred approach since it defines the plexus and adjacent structures in detail. 41 …”
Section: Celiac Plexus Block (Cpb) and Splanchnic Plexus Blockmentioning
confidence: 99%
“… 40 Recently, endoscopic ultrasound (EUS) has become a preferred approach since it defines the plexus and adjacent structures in detail. 41 …”
Section: Celiac Plexus Block (Cpb) and Splanchnic Plexus Blockmentioning
confidence: 99%
“…4,10 Endoscopic techniques have more recently been reported. 11 As stated by Mercadante and Nicosia, 4 the anterior approach might theoretically reduce the risk of neurologic injury, but available data are limited. In 1988, Montero Matamala et al 12 described a new computed tomography-guided approach of the celiac plexus, opening the door of the anterior approaches, and in 1989, the same authors reported the use of ultrasound guidance instead of computed tomography guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The real‐time guidance and color Doppler imaging by EUS made the procedure easier and safer, resulting in greater pain relief compared with other modalities, such as computed tomography and fluoroscopy. Moreover, a new technique, EUS‐guided direct ganglia neurolysis, was recently developed and provided greater pain relief than the conventional EUS‐CPN . However, such EUS‐guided celiac plexus interventions are not widely applied, probably due to their limited long‐term analgesic effects and development of better opioid analgesics.…”
Section: Eus‐guided Celiac Plexus Interventionmentioning
confidence: 99%
“…Moreover, a new technique, EUSguided direct ganglia neurolysis, was recently developed and provided greater pain relief than the conventional EUS-CPN. 9 However, such EUS-guided celiac plexus interventions are not widely applied, probably due to their limited long-term analgesic effects and development of better opioid analgesics.…”
Section: Eus-guided Celiac Plexus Interventionmentioning
confidence: 99%